2019
DOI: 10.1101/752949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals functional heterogeneity and sex differences of glioma-associated brain macrophages

Abstract: 13Brain resident and infiltrating innate immune cells adapt a tumor-supportive phenotype in the 14 glioma microenvironment. Flow cytometry analysis supported by a single-cell RNA 15 sequencing study of human gliomas indicate considerable cell type heterogeneity. It remains 16 disputable whether microglia and infiltrating macrophages have the same or distinct roles in 17 supporting glioma progression. Here, we performed single-cell transcriptomics analyses of 18 CD11b+ cells sorted from murine syngeneic gliomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 73 publications
4
33
0
Order By: Relevance
“…8a, b, d). In addition and consistent with emerging descriptions of activated myeloid cell signatures in the glioma microenvironment, we also observed a population of glioma-associated microglia 107,109,110 (microglia 2 (cluster 2)) that express Ccl2, Ccl12, Ifitm3, and Il1β ( Fig. 10e and Supplementary Fig.…”
Section: Controlsupporting
confidence: 89%
See 2 more Smart Citations
“…8a, b, d). In addition and consistent with emerging descriptions of activated myeloid cell signatures in the glioma microenvironment, we also observed a population of glioma-associated microglia 107,109,110 (microglia 2 (cluster 2)) that express Ccl2, Ccl12, Ifitm3, and Il1β ( Fig. 10e and Supplementary Fig.…”
Section: Controlsupporting
confidence: 89%
“…10g). As predicted, we observed a transition from IL-33 enriched inflammatory monocytes 100 (marked by expression of Ccr2, Ifitm2, and Ifitm3) to differentiating BMDM and then to glioma-associated BMDM 107,110,111 (marked by expression of Apoe, Hexb, and Cd81) consistent with a pro-tumorigenic environment. In addition, a gradual down regulation of ribosomal genes (e.g., Rpl and Rps) is seen within the trajectory, a feature akin to the myeloid lineage differentiation pattern observed by Athanasiadis and colleagues 112 and consistent with a recent study that has mapped the diversity of non-parenchymal brain macrophage 111 .…”
Section: Plbd1supporting
confidence: 85%
See 1 more Smart Citation
“…Importantly, infiltration of blood-derived macrophages instead of microglia correlates with poor survival in low-grade glioma (Müller et al, 2017 ). ScRNAseq of mouse glioma shows that there are eight to nine clusters of microglia and three clusters of blood-derived macrophages (Ochocka et al, 2019 ). Among the microglia subsets, there are three major subgroups: one with high expression of homeostatic microglia signature genes, one with high transcriptional activity of gene that inhibit nuclear factor kappa B (NFκB) signaling, and one with increased expression of genes for antigen presentation (Ochocka et al, 2019 ).…”
Section: Heterogenous Macrophages and Microglia In Gliomamentioning
confidence: 99%
“…In recent years, scRNA-seq has been extensively used to understand the intratumoral genetic landscape in glioblastoma, medulloblastomas, kidney cancer, colorectal cancer, and other types of cancers [20,21,24,59,[77][78][79][80][81][82][83][84][85][86][87][88]. A recent scRNA-seq study provided a blueprint for glioblastoma and found that malignant cells exist in four primary cellular states, and the relative frequency of cells in each state varied according to the tumor microenvironment [89].…”
Section: Profiling Heterogeneous Cell Populations From Different Tumorsmentioning
confidence: 99%